Draft Annual Plan 1993-94 Andhra Pradesh Volume-I (General) - Government of Andhra Pradesh (Government of Andhra Pradesh, 1992)
The Draft Annual Plan 1993-94 for Andhra Pradesh presents a strategic blueprint for state-wide development, emphasizing critical sectors such as energy, irrigation, agriculture, social services, and infrastructure. With a proposed outlay of Rs. 1,851 crores, the plan prioritizes energy generation (Rs. 550.43 crores), irrigation and flood control (Rs. 440.00 crores), and social services (Rs. 433.98 crores) to address both immediate and long-term economic challenges. Key economic indicators highlight a population of 6.63 crore with a work participation rate of 45.3%, an NSDP growth of 2.6%, and per capita income of Rs. 5,596, reflecting modest but steady development. Infrastructure initiatives include the expansion of APSRTC transport services, significant irrigation projects such as Sriramsagar and Srisailam canals, and enhanced power generation capacity at 4,972 MW. The plan also allocates substantial resources for human development, including literacy improvement, rural health, sanitation, and housing for weaker sections, along with targeted support for agricultural labor through welfare programs. Special Area Development Programmes focus on marginalized regions, including coastal and remote areas, while the Minimum Needs Programme emphasizes education and rural health. Enhanced financial planning supports public distribution, banking expansion, and effective management of urban slums. Overall, the Draft Annual Plan reflects a holistic, data-driven approach aimed at sustainable socio-economic growth, infrastructure enhancement, and improved quality of life across Andhra Pradesh, aligning state priorities with national development objectives.
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh, Hyderabad December 1992
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh, Hyderabad December 1992
Keywords: Andhra Pradesh; State Plan; Energy Development; Irrigation Projects; Social Services; Infrastructure; Agriculture; Flood Control; Public Distribution; Literacy; Health Services; Special Area Development